A Temporal PROTAC Cocktail‐Mediated Sequential Degradation of AURKA Abrogates Acute Myeloid Leukemia Stem Cells. Issue 22 (2nd June 2022) - Liu, Fang; Wang, Xuan; Duan, Jianli; Hou, Zhijie; Wu, Zhouming; Liu, Lingling; Lei, Hanqi; Huang, Dan; Ren, Yifei; Wang, Yue; Li, Xinyan; Zhuo, Junxiao; et al.
Abstract: AURKA is a potential kinase target in various malignancies. The kinase‐independent oncogenic functions partially disclose the inadequate efficacy of the kinase inhibitor in a Phase III clinical trial. Simultaneously targeting the catalytic and noncatalytic functions of AURKA may be a feasible approach. Here, a set of AURKA proteolysis targeting chimeras (PROTACs) are developed. The CRBN‐based dAurA383 preferentially degrades the highly abundant mitotic AURKA, while cIAP‐based dAurA450 degrades the lowly abundant interphase AURKA in acute myeloid leukemia (AML) cells. The proteomic and transcriptomic analyses indicate that dAurA383 triggers the "mitotic cell cycle" and "stem cell" processes, while dAurA450 inhibits the "MYC/E2F targets" and "stem cell" processes. dAurA383 and dAurA450 are combined as a PROTAC cocktail. The cocktail effectively degrades AURKA, relieves the hook effect, and synergistically inhibits AML stem cells. Furthermore, the PROTAC cocktail induces AML regression in a xenograft mouse model and primary patient blasts. These findings establish the PROTAC cocktail as a promising spatial‐temporal drug administration strategy to sequentially eliminate the multifaceted functions of oncoproteins, relieve the hook effect, and prevent cancer stem cell‐mediated drug resistance. Abstract : This study establishes the PROTAC cocktail of CRBN‐based dAurA383 and cIAP‐based dAurA450 as a promising spatial‐temporal drug administration strategy to sequentially eliminate the multifaceted functions of mitotic AURKA and interphase AURKA, relieve the hook effect, and prevent cancer stem cell‐mediated drug resistance in acute myeloid leukemia. PROTAC cocktail strategy is proposed to be a second generation of PROTACs.